Donne traducono donne. Paola Faggioli traduttrice di Aino Kallas - Sessa, Delfina (fi=Turun yliopisto|en=University of Turku|, 2023)
Translating women. Aino Kallas’s translator Paola Faggioli This study focuses on the cultural interaction that enabled the translation and publication of Aino Kallas’s trilogy Surmaava Eros in Italy during the Fascist regime. The trilogy by the Finnish born, Estonian resident Kallas revolves around three women who rebel against the social norms of the time and hence are punished with death. To analyse the relations between the different agents involved in the translation and publication of the trilogy, the study draws on Susan Bassnett and André Lefevere’s theoretical thinking. Interaction between agents, groups and cultures is seen as deeply embedded in their historical, political, ideological and social milieu. Methodologically, the study is informed by microhistory: an approach that in Translation Studies has been applied by scholars like Anthony Pym, Outi Paloposki and Jeremy Munday. The material of the research includes extensive archival sources, paratextual materials as well as the translated texts. As a background, the study explores relevant aspects of the development of the publishing industry in Italy under Fascism, with a specific focus on the translator and on translation practices. In addition, an overview of the cultural and political intercourse between Italy and Finland is provided with a view to investigate some motivations underlying the interest in Finnish literature and culture and to explore what kind of an image the cultural initiatives were aiming to convey to the Italian reader. The study attempts at unravelling the mystery surrounding the translator, Paola Faggioli. As a woman, she was in an inferior position under the patronage of Paolo Emilio Pavolini, translator of the Finnish epic Kalevala and father of the prominent fascist politician Alessandro. On text level, the study aims at identifying the presence of the translator and exploring her choices. The central part of the dissertation tries to unravel the connection between author and translator by shedding light on the negotiations that led to the publication of the trilogy. The sources uncover a cooperation of key mediators motivated by personal reasons. As for the central figure of this study, Paola Faggioli, my findings reveal a complex personal history entangled with power relations: despite enjoying the protection of a fascist patron, she was still a woman in conflict with the social norms. Faggioli emerges, however, as a professional and competent translator and linguist who made her own choices and did not depend on her patron in terms of language competence and translation skills. The case of a marginal literature can uncover networks and issues which do not necessarily emerge in the case of more familiar and larger-scale book markets. This study sheds light on some of the practices adopted by Italian publishers when they negotiated with foreign authors; it uncovers some core aspects of the translation of Finnish literature in Italy and it sets in high relief the career of a woman translator in the period examined. Other agents, their personality and role in intercultural exchanges between Italy and Finland also emerge within the wider theme of the relations between the two countries and the role of ideology and politics in cultural exchange.

Naiset tulkitsevat naisia. Paola Faggioli Aino Kallaksen kääntäjänä Tämän tutkimuksen aiheena on kulttuurinen vuorovaikutus, joka mahdollisti Aino Kallaksen Surmaava Eros -trilogian kääntämisen ja julkaisemisen Italiassa fasistihallituksen aikana (1922–1943). Kallaksen virolaisaiheisen, historiallisen trilogian päähenkilöinä on kolme naista, jotka haastavat sen kapean roolin, jonka aika ja yhteisö ovat naisille määrittäneet, ja jotka sen seurauksena tuomitaan kuolemaan. Väitöstutkimuksessa eri toimijoiden välisiä suhteita analysoidaan Susan Bassnettin ja André Lefeveren teoreettisen ajattelun pohjalta. Toimijoiden, ryhmien ja kulttuurien välinen vuorovaikutus kytketään tiiviisti ajan historialliseen, poliittiseen ja aatteelliseen ympäristöön. Lähestymistapa ammentaa mikrohistoriasta; samaa mikrohistoriallista lähestymistapaa ovat soveltaneet käännöstutkimuksen alalla aiemmin muun muassa Anthony Pym, Outi Paloposki ja Jeremy Munday. Tutkimusaineisto sisältää arkistomateriaaleja ja paratekstejä sekä kohdekieleen käännetyt tekstit. Tutkimus asetetaan historialliseen ja kulttuuriseen kehykseen esittelemällä Italian fasismin aikaisen kustannusteollisuuden kehityksen pääpiirteitä. Tutkimuksessa keskitytään kääntäjän rooliin, kääntämiseen liittyviin käytäntöihin ja periaatteisiin sekä Italian ja Suomen väliseen poliittiseen ja kulttuuriseen vuorovaikutukseen. Analyysissä selvitetään, miksi suomalainen kirjallisuus ja kulttuuri nousivat kiinnostuksen kohteeksi ja minkälainen kuva Suomesta ja suomalaisista haluttiin antaa italialaiselle yleisölle kulttuuritapahtumien ja kirjallisuuden välityksellä. Väitöstutkimus haluaa tuoda valokeilaan italiantaja Paola Faggiolin, naisen, joka on jäänyt mentorinsa Paolo Emilio Pavolinin varjoon – Pavolinin, joka oli akateemikko, Kalevalan arvostettu kääntäjä ja myös fasistipuolueen johtaja Alessandro Pavolinin isä. Tekstejä analysoimalla pyritään tavoittamaan merkkejä Faggiolista kääntäjänä ja tutkimaan hänen käännösvalintojaan. Tutkimuksessa etsitään lisäksi Kallaksen ja Faggiolin välistä yhteyttä jäljittämällä kanssakäymisiä ja tekijöitä, jotka johtivat tässä tutkimuksessa tarkasteltavan trilogian julkaisemiseen Italiassa. Lähteet paljastavat, että avainhenkilöiden henkilökohtaiset vaikuttimet olivat merkittävä tekijä käännös- ja julkaisuprosessissa. Tutkimuksessa tuodaan esiin myös Faggiolin valtasuhteiden varjostama asema: vaikutusvaltaisen mentorinsa suojeluksesta huolimatta hänen asemansa naimisissa olevan mentorinsa rakastajattarena ja heidän yhteisen lapsensa yksinhuoltajana oli yhteiskunnallisten normien vastainen. Kääntäjänä hän osoittautuu päteväksi ja itsenäiseksi ammattilaiseksi, jonka ei tarvinnut nojata mentorinsa kieli- ja käännöstaitoon. Vähemmän tunnettu kirjallisuus voi paljastaa verkostoja ja näkökulmia, jotka eivät välttämättä käy ilmi suurten painosten kirjamarkkinoita tarkasteltaessa. Väitöstutkimus nostaa esiin naiskääntäjän uran fasismin aikaisessa Italiassa, valottaa italialaisten kustantajien menettelytapoja heidän neuvotellessaan ulkomaalaisten kirjailijoiden kanssa ja tarjoaa havaintoja keskeisistä kysymyksistä suomalaisen kirjallisuuden kääntämisestä Italiassa. Tutkimuksessa tarkastellaan laajemmin myös Italian ja Suomen välisiä suhteita sekä ideologian ja politiikan vaikutusta kulttuurivaihtoon. Tällöin näkyviin tulee myös muita toimijoita, joilla on roolinsa kulttuurien välisessä vuorovaikutuksessa.